Characteristics of Patients with Meningeal Carcinomatosis Combined with Myelopathy - Jiao L; Wei M; Fu Y (Neuropsychiatric Disease and Treatment, 2022)
Lidong Jiao,1 Min Wei,1 Yongjuan Fu2 1Department of Neurology, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People’s Republic of China; 2Department of Pathology, Xuanwu Hospital, Capital Medical University, Beijing, 100053, People’s Republic of ChinaCorrespondence: Lidong Jiao Department of Neurology, Xuanwu Hospital, Capital Medical University, No. 45 ChangChun Street, XiCheng District, Beijing, 100053, People’s Republic of China Tel +86-10-83198814 Email jlddr2021@163.comObjective: To explore the disease manifestations and radiological characteristics of patients with meningeal carcinomatosis (MC) combined with myelopathy.Patients and Methods: The detailed medical information of patients who suffered from MC with myelopathy in record system were collected and reviewed.Results: In these patients, five cases were male and two cases were female. The age was from fifteen to fifty-seven years. In the course of disease, tumor cells were discovered in cerebrospinal fluid of three patients and in biopsy samples of four patients. Cerebrospinal fluid (CSF) test results showed white blood cell counts increased in seven patients, protein increased in six patients and glucose reduced in five patients. In addition, MRI revealed that the white matter abnormalities showed in all cases and pia mater was enhanced in four patients, meningeal enhanced was observed in three patients. All patients were given appropriate therapy during hospitalization. Follow-up result showed that all patients passed away two to five months after diagnosis.Conclusion: MC causes spinal membrane, spinal nerve root to be involved besides, also can produce the matter of myelopathy. Early detection of intramedullary lesion is conducive to strengthening the awareness of the diagnosis of MC.Keywords: meningeal carcinomatosis, myelopathy, histopathological investigation, CSF cytology